Dylematy kultury terminalnej - Mazurek, Marcin (Er(r)go. Teoria - Literatura - Kultura, 2002)
Marcin Mazurek's review of "Terminal Identity. The Virtual Subject in Postmodern Science Fiction" by Scott Bukatman(1993).